The Effect of Air Traffic Controller Work Stress on Decision-Making Quality in the Tower and Approach/Terminal Units of the Jakarta Air Traffic Service Center - Dara Puspita Sari; Rany Adiliawijaya Putriekapuja; Ichyu Machmiyana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Aviation safety is strongly influenced by the performance of Air Traffic Controllers (ATC), particularly in operational decision-making. High air traffic density, time pressure, shift work, and safety responsibilities can generate work-related stress that may affect the quality of ATC decision-making. This study aims to analyze the effect of work stress on the quality of decision-making among Air Traffic Controllers at the Tower and Approach/Terminal units of the Jakarta Air Traffic Service Center (JATSC). The research employs a quantitative approach using a correlational method. The sample consists of 39 active ATC selected through purposive sampling. Data were collected using Likert-scale questionnaires measuring work stress and decision-making quality. Data analysis included validity and reliability tests, statistical assumption testing, and correlation and simple linear regression analysis. The results of this study are expected to provide empirical evidence regarding the relationship between work stress and ATC decision-making quality and to serve as an evaluation reference for air navigation service providers in improving safety performance.